Understanding The Communication Behaviour Differences Between Father and Son in Divorced and Intact Families - Muhammad Iman Adi Perkasa; Drs. Hj. Sri Widowati Herieningsih, MS (Interaksi Online, 2016)
Intact families have a strong structure bond in legal marital status or religion, as well as consisting of father, mother, and children. Conflict within both parents frequently make the intact structure could not sustain the marriage. On divorced and intact families, the relationship between father and son was always in the spotlight, partly because of the communication competence father tend to be lower than the mother. However, relationship between father and son on intact family rated have more effective communication behavior than in divorced families. This is reinforced by the data which states the existence significant association between divorced and juvenile delinquency figures dominated by sons. This study aims to determine and describe the subjective experiences of the communication differences between father and son in divorced and intact families, using descriptive qualitative method with phenomenological analysis. This ressearch used, Self-Concept Theory, Family Patterns Theory, Relational Dialectics Theory, Communication Relational Theory and Gender Stereotype Theory. The study found in divorced family : 1) Self disclosure tend to be low, thereby affecting son’s to unlock the difficulties in communication between fathe and son whereas not up to the private sphere as friendship and romantical communication. 2) The low communication intensity between father and son, causes the uncomfortable feel in every son to every communication process they do. 3) The low communication intensity also resulted depth and not exhaustive discussion or dialogue and covering only a simple daily communication between them. 4) Dialogue between father and son which tend directly to the subject matter, resulted content significance levels concept, influenced by low context culture.